2013
DOI: 10.1177/2325967113505433
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Term Results After Treatment of Recalcitrant Lateral Epicondylitis

Abstract: Background:Recalcitrant lateral epicondylitis (elbow extensor–origin tendinosis) is a common cause of elbow pain with many treatment options. In the present study, the medium-term results after open release and radiofrequency microtenotomy are reported.Hypothesis:Microtenotomy would provide long-term pain relief that was as good as the open release method.Study Design:Prospective, randomized trial.Methods:Twenty-four patients randomized to either open release or microtenotomy were assessed after 5 to 7 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 38 publications
(81 reference statements)
0
38
0
Order By: Relevance
“…The 9 articles represented only 8 studies because outcomes from 1 study were published for 2 different follow-up time periods in 2 separate papers. [16,17]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 9 articles represented only 8 studies because outcomes from 1 study were published for 2 different follow-up time periods in 2 separate papers. [16,17]…”
Section: Resultsmentioning
confidence: 99%
“…Five studies measured grip strength, out of which 4 were randomized controlled trials. [13,15–17] All 5 reported an improvement in grip strength. [12,15–17,19] Two studies observed an increase in grip strength, but was either not significant or they did not provide statistical analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In the literature, several open techniques were proposed, including extensor release and/or debridement, extensor fasciotomy, denervation of the lateral epicondyle, epicondylar resection with anconeus muscle transfer, and the Garden procedure with lengthening of the ECRB. [11][12][13][14][15][16] Among them, extensor release and/or debridement which was originally described as "excision of diseased tissue at the origin of the ECRB tendon" 17 is one of the most well accepted techniques. Recently, arthroscopic treatment gained increasing popularity as a less invasive alternative of traditional open surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, open and arthroscopic release/ debridement of TE were the most acknowledged techniques 11,13,14,16,22,30 for the management of TE, and some systematic reviews were published to compare the outcome of conventional open and arthroscopic surgery, 27,31,32…”
Section: Introductionmentioning
confidence: 99%